Legal Construction of Interfaith Marriage in Indonesian Pluralism Context: Analysis of Regulation and Practice - Candra Andreansah Harahap; Agung Syarifudin; Fadlan Fadlan (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This research examines the legal construction of interfaith marriage in Indonesia within its pluralistic context. Through socio-legal analysis, it explores current regulations, implementation practices, and challenges in accommodating interfaith marriages under Indonesian law. The study analyzes Marriage Law No. 1/1974, Civil Administration Law, and relevant court decisions, revealing gaps between constitutional rights of religious freedom and existing marriage regulations. Research methods include document analysis, case studies, and comparative legal analysis with other pluralistic societies. Findings indicate significant challenges in legal recognition and civil registration of interfaith marriages, impacting citizens' constitutional rights. The study proposes legislative reforms and administrative improvements to better accommodate religious diversity while maintaining legal certainty. This research contributes to the ongoing discourse on legal pluralism and religious freedom in Indonesian marriage law.